Exploring Potential Drug-Drug Interactions: A Cross-Sectional Study of 1 Million e-Prescriptions Across Medical Specialties in Shiraz, Iran (2021-2024). - Porbaha, Pedram; Hasannejad, Mohammad; Ahvar, Negar; Shafiekhani, Mojtaba; Abolpour, Nahid; Sharifi, Mehrdad (Iranian Journal of Medical Sciences, 2026)
Background: Drug-drug interactions (DDIs) are among the most important medical errors that can lead to adverse effects, increased toxicity, or reduced treatment efficacy. The frequency and severity of DDIs vary across specialties. However, studies covering multiple specialties in Iran are few and not up-to-date. This study aims to fill this gap by offering a large-scale, multi-specialty analysis of DDIs in Iran using real-world e-prescription data. Methods: This study analyzed pharmacological DDIs in 1,049,769 e-prescription records from Shiraz, Iran, spanning from November 2021 to February 2024. We used Lexicomp® DDI checker software and Python programming language to identify the most prevalent DDIs overall, the top contributing drug specialties for each of those DDIs, the specialties with the highest rates of potential DDIs, and the most prevalent DDI within each specialty. Results: The analysis revealed that 38.77% of prescriptions contained at least one C, D, or X DDI. Dexamethasone, ketorolac, quetiapine, and aspirin were the drugs most commonly involved. The most frequent DDIs occurred between aprepitant and dexamethasone, ketorolac, and naproxen, aprepitant and doxorubicin, prednisolone, and tacrolimus, and diclofenac sodium and ketorolac. The medical specialties with the highest incidence of D or X level DDIs were rheumatology, endocrinology, orthopedics, oncology, internal medicine, emergency services, and psychiatry. The average counts of D or X DDIs per prescription were 0.53, 0.41, 0.40, 0.40, 0.26, 0.24, and 0.23, respectively. Conclusion: This study underscores the need for provider vigilance and proactive measures, such as training and e-prescription alerts, to ensure patient safety.